FORMULASI KRIM MINYAK ZAITUN (OLEA EUROPEA) DENGAN KOMBINASI EMULGATOR TRIETANOLAMIN (TEA) DAN ASAM STEARAT SEBAGAI MOISTURIZER - Diana Handoyo (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2024)
This research is entitled Formulation of Olive Oil Cream (Olea Europea) with a Combination of Triethanolamine Emulgator (TEA) and Stearic Acid as Moisturizer. About 30% of adults have dry skin, and as people age, this frequency will rise. One moisturizer that helps avoid dry skin is olive oil. The purpose of this study is to create an olive oil cream that contains stearic acid as a moisturizer and TEA emulsifier. Emulsification is the process used to make creams, and it is followed by organoleptic, morphological, pH, and viscosity analyses. Along with the rise in emulsifiers, pH F1 (6.67), F2 (7.09), and F3 (7.58), and viscosity F1 (34.8 cps), F2 (1520 cps), and F3 (1636 cps), these formulas yield various physical assessments. The pH and viscosity of the olive oil cream will rise in proportion to the emulsifier concentration utilized.